The years shall run like rabbits. - Barnes, Martin, 1971- (Aperture, 2015)
Over the last 20 years, Hellen van Meene has produced a complex body of work, offering a contemporary take on photographic portraiture. Characterized by her exquisite use of light, formal elegance and psychological tension, her depictions of girls and boys on the cusp of adulthood demonstrate a clear aesthetic lineage to seventeenth-century Dutch painting. Van Meene captures the intimacy in the photographer-subject relationship, bringing out a sense of honesty and vulnerability from within her models and highlighting the beauty of imperfection. She carefully poses her subjects in their environments to emphasize their fragility, adding a palpable tension to the photographs. At the same time, she captures them at deeper, more introspective moments, masterfully moving between the staged nature of the portraits and the real experiences of her subjects. The combination of van Meene's instinctive understanding of the universality of adolescent experience and the highly intimate collaboration between photographer and model makes for powerful portraits that resonate long after viewing. This book brings together more than 250 images, for the most comprehensive presentation of the artist's work to date.